Acai Residue as an Ecologic Filler to Reinforcement of Natural Rubber Biocomposites - Araújo, Samara S. [UNESP]; Santos, Gleyson T.A. [UNESP]; Tolosa, Gabrieli R. [UNESP]; Hiranobe, Carlos T. [UNESP]; Budemberg, Eduardo R. [UNESP]; Cabrera, Flávio C. [UNESP]; da Silva, Michael J. [UNESP]; Paim, Leonardo L. [UNESP]; Job, Aldo E. [UNESP]; dos Santos, Renivaldo J. [UNESP] (FapUNIFESP (SciELO), 2023)
The biodiversity of plant resources is a renewable source that can use as a sustainable component in various applications. The use of vegetable waste as a filler element in polymeric composites is part of the solid waste management policy and the sustainable development of agribusiness. In this work, the natural rubber composites were prepared with acai seed in proportions of 0, 10, 20, 30, 40, and 50 phr (per hundred rubber). The composites were homogenized in an open cylinder mixer and characterized by rheometric, morphological, mechanical, and thermal tests. The addition of the organic fillers significantly reduced the vulcanization process time. Thermogravimetric analysis and infrared spectroscopy showed that the composites were thermally stable and showed no structure changes after the vulcanization process, respectively. The Lorenz-Parks method's evaluation of matrix/filler interactions showed a strong interaction between NR/Acai. The new biocomposite can replace non-ecological composites economically and sustainably.
Keywords: Acai; biocomposites; Lorenz-Parks; Mooney-Rivlin; sustainability; vulcanization